Senegal - Sustainable and Participatory Energy - World Bank (Washington, DC, 2012)
The Sustainable and Participatory Energy Management project - PROGEDE was implemented by the government between 1997 and 2004. From project preparation to supervision the World Bank worked in close collaboration with Dutch Co-operation (DGIS). At the time of project preparation, forest-based traditional fuels (firewood and charcoal), mainly used for household cooking purposes, represented 53 percent of Senegal's final energy consumption, and 76 percent of charcoal consumption was in the principal urban areas. Over the years, the operation of the charcoal industry had resulted in (i) the gradual loss of forest cover (approximately 30,000 ha per year) and thus of the ecosystem's carbon sequestration capacity and biodiversity; (ii) the degradation of the rural environment (particularly soils); (iii) the impoverishment of the rural areas; (iv) an acceleration of rural exodus; and (v) a massive transfer of wealth from the rural communities to a few urban-based woodfuel traders.